The Mediating Role of Organizational Commitment on the Relationship Between Transformational Leadership and Employee Retention for Cafés in Surabaya - Stefanie Saphira; Christian Wibisono (iBuss Management, 2023)
Rapid expansion of globalization has made businesses around the world to be more competitive with its rapid changes and opportunities. This worries Indonesia’s food and beverage industry as it is one of the top contributors to the Indonesian economy. The food and business industry covers various forms starting from products such as snacks to services such as cafés or restaurants. This study will focus on the cafés, specifically in Surabaya, East Java, as it is one of the backbones of Indonesia's economy and one of the most common forms of the food and beverage industry. Cafés need to pay attention to their employee retention as it can increase their commitment as well as their skills, thus, ultimately increasing overall productivity. In addition to employee retention, this study would focus on the mediating effect of organizational commitment between transformational leadership towards employee retention. This study model will use simple random sampling by spreading questionnaires throughout social media platforms. Then, the PLS-SEM method will be used to evaluate 334 valid respondents. Results found from the analysis indicate that there is a partial mediating effect of organizational commitment between transformational leadership towards employee retention. Moreover, it is also revealed that there is a positive relationship between transformational leadership and employee retention and between transformational leadership and organizational commitment.Keywords: Transformational leadership, Employee retention, Organizational commitment, Cafés, Surabaya.